ChemInform Abstract: Microwave‐Assisted C—N and C—S Bond‐Forming Reactions: An Efficient Three‐Component Domino Sequence for the Synthesis of Sulfoether‐Decorated Imidazo[1, 2‐a]pyridines. Issue 35 (September 2015) - Zhan, Haiying; Cao, Hua; Qiu, Huifang; Li, Naiying; Chen, Longbin; Liu, Jingyun; Cai, Huiyin; Tan, Jingwen
Abstract Highly functionalized imidazopyridines are efficiently obtained by three‐component one‐pot reaction of 3‐phenylpropiolaldehyde (III), a wide range of pyridin‐2‐amines (I), and various thiols.